PWE-032 Hemospray for acute upper gastrointestinal bleeding – a single centre experience. (22nd June 2015) - Widlak, MM; Wijesinghe, H; Siau, K; Molitor, T; Quraishi, MN; Armstrong, M; Troth, T; Iqbal, T; Goh, J
Abstract : Introduction: Upper gastrointestinal bleeding (UGIB) is the commonest medical emergency managed by the Gastroenterologists. Despite of familiarisation with a variety of medical and endoscopic strategies to treat underlying aetiologies, rebleeding and mortality rates remain high. A novel agent, known commercially as Hemospray, has recently been licensed for use in non-variceal upper gastrointestinal bleeding (NVUGIB). Method: The aim of this study was to assess the effectiveness of Hemospray therapy, either as primary endotherapy, or as part of salvage endotherapy in NVUGIB, when conventional measures to achieve haemostasis were deemed insufficient. All patients treated with Hemospray at University Hospital Birmingham, since its introduction to the Unit in 2013, were retrospectively identified using the Unisoft endoscopy database. Data on the indications for Hemospray use, and application in conjunction with other therapeutic modalities were collected. Outcomes including mortality, primary haemostasis and re bleeding rates were analysed. Results: Hemospray was applied in 48 patients with NVUGIB (median age 63 years, 70% male). Four patients had Hemospray used on more than one occasion. Causes of bleeding included peptic ulcer disease 29/48 patients (60.5%), other non variceal upper GI pathology 13/48 (27%) and post variceal banding oesophageal ulcers 6/48 (12.5%). Hemospray was used as primary endotherapy in 42/48 patients (87.5%), achieving initial haemostasis in 40/42 cases (95%). 6/48 patients (12.5%) received Hemospray as salvage therapy following a rebleed after treatment with standard primary therapy. Rebleeding within 7 days occurred in 4/42 patients (9.5%); two of them received Hemospray as monotherapy. 30-day mortality in this patient cohort was 9/48 (19%). There were no documented complications of Hemospray therapy. Conclusion: Hemospray is a safe and effective endoscopic therapy in achieving initial haemostasis, both as primary and salvage therapy, and either as monotherapy or in combination with other endoscopic modalities in a wide variety of upper GI pathologies, including post variceal banding oesophageal ulcers. We have found this to be a useful adjunct in the management of NVUGIB when conventional techniques have failed. However, further studies are needed to define its cost-effectiveness in the acute hospital setting. Disclosure of interest: None Declared.